TECHNOLOGICAL INVESTIGATION FOR SINTERED Nd-Fe-B MAGNETS Pham Thi Thanh - Thanh, Pham Thi; Yen, Nguyen Hai; Dan, Nguyen Huy (Vietnam Journal of Science and Technology, 2014)
1, Nguyen Hai Yen1, Nguyen Huy Dan1. 1 Institute of Materials Science, Vietnam Academy of Science and Technology 18 Hoang Quoc Viet, Cau Giay, Ha Noi, Vietnam. Email: thanhpt@ims.vast.ac.vn ABSTRACT Sintered Nd-Fe-B magnets are used more and more in practice such as motors, generators, ore-separators, magnetic cushions... To ful-fill requirements of various aspects of practical applications, further enhancement of magnetic properties and optimization of fabrication technology of these magnets are still concerned to study. In this report, we present the results of investigation of influence of grinding, sintering and annealing processes on magnetic properties of the anisotropic permanent Nd-Fe-B magnets. We have established a low cost, practical applicable technological process to manufacture Nd-Fe-B magnets in pilot scale with maximum energy product above        35 MGOe. Keywords. anisotropic sintered magnet, coercivity, maximum energy product (BH)max, Nd-Fe-B alloy, hard magnetic material.